2012
DOI: 10.1002/hed.23101
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of transoral robotic supraglottic laryngectomy

Abstract: In this preliminary study, TORS supraglottic laryngectomy was a safe procedure with good functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
69
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 44 publications
1
69
1
2
Order By: Relevance
“…Negative margins were obtained in all patients and no local recurrences on 2-year follow-up. Ozer and colleagues report largely similar results in a series of 13 patients [ 20 ]. All achieved negative margins but one patient required conversion to an open approach due to extensive pre-epiglottic space invasion (Fig.…”
Section: Laryngologymentioning
confidence: 59%
See 1 more Smart Citation
“…Negative margins were obtained in all patients and no local recurrences on 2-year follow-up. Ozer and colleagues report largely similar results in a series of 13 patients [ 20 ]. All achieved negative margins but one patient required conversion to an open approach due to extensive pre-epiglottic space invasion (Fig.…”
Section: Laryngologymentioning
confidence: 59%
“…An elective perioperative tracheostomy rate of 12.4 % was encountered while only a total of four patients (2.3 %) remained with a tracheostomy at 12 months follow up. For patients undergoing primary TORS treatment, a gastrostomy dependency [ 20 ] of 5 % was encountered. Positive surgical margins were noted in 3.8 % of patients with oropharyngeal tumors, a rate that the authors feel compares favorably with other transoral or open techniques.…”
Section: Head and Neck Surgerymentioning
confidence: 99%
“…In the TRS series of Kayhan et al (28) on 13 patients with T1-T2 supraglottic cancer, they reported that the average blood loss was below 40 mL in addition to the advantages of the short length of transition to oral feeding, short length of hospitalization, and no need for tracheotomy. In literature, local control rates after TRS supraglottic laryngectomy are reported to range between 80% and 100% (29)(30)(31)(32). The robotic approach is used as an alternative to TLM also in early-stage glottic cancers (33).…”
Section: Clinical and Research Impactsmentioning
confidence: 99%
“…There has been an increasing concern to reduce morbidity (without jeopardizing oncological safety) and to improve quality of life and patient satisfaction. In recent years, there has been notable progress in minimally invasive video-assisted surgeries associated or not with technological equipment, such as laser and motorized instruments, which could facilitate these procedures (13)(14)(15).…”
mentioning
confidence: 99%